Ukraine : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The main objectives of the country procurement assessment are to diagnose the public procurement system in Ukraine, assess compatibility of the country's laws, policies and procedures with international best practices, review compliance with the procurement laws and regulations and identify areas for improvement of the procurement system in Ukraine. With due recognition of the considerable achievements made to date, the Government of Ukraine continues to face challenges in the further development of the country's public procurement system. The most significant of these relate to: further development of the legislative framework; improving procurement procedures and practices; increasing competition; more effective and consistent implementation of the Public Procurement Law; combating procurement-related corruption; developing the institutional capacity of procuring entities; improving the professional qualifications of public-sector staff; and increasing compatibility with international bodies of procurement law, including those of the European Union (EU) and the World Trade Organization (WTO). This report is organized as follows: Section I of the CPAR report describes Ukraine's existing public procurement system, including its policies, procedures and practices as well as institutional and organizational framework. It assesses the implementation aspects and makes recommendations for reforming the system in major areas. Section II identifies issues in the implementation of projects financed by the World Bank. The performance of the private sector in the procurement process of the country, with its emerging issues, is described in Section III. Finally, Section IV suggests an action plan with key recommendations for implementation by the Government. Attachments list a summary of different provisions in the PPL; strengths and weaknesses in the public procurement system and provisions in the Law discussed with the PPO to further improve the legal framework; and a technical assistance program for consideration by the Bank.